Analisis Kinerja Simpang Bersinyal Jalan A. Yani – Jalan Baco Kabupaten Tabalong - Muhammad Arsyad; Dewi Septiana (Jurnal Teknologi Berkelanjutan, 2021)
This study aims to analyze the performance of the intersection of Jalan A. Yani - Jalan Baco, Tabalong Regency with the direct observation method in the field and data analysis following the standard guidelines of the Indonesian Road Capacity Manual (MKJI) method and assisted by the KAJI software. From the analysis and calculation results, the current data for the peak hour that occurs is 17.20－18.20. The results obtained from the existing conditions of the intersection include Degree of Saturation (DS) = 0.525, Intersection Delay (D) = 9.28, and Queuing Opportunity (Qp) = 19%, with service level of B (still meeting applicable requirements). Then forecasting is done so that the 5-year intersection does not meet the requirements with DS = 0.853, D = 14.19, and Qp = 44%. The alternative solution used for the next 5 years is to change the unsignalized intersection to a 3-phase signalized intersection (with widening) which is seen from the average delay of the intersection of 20.95 seconds/pcu, the degree of saturation is 0.